The Areal Typology of Languages of the Americas (ATLAs) database - David Inman; Natalia Chousou-Polydouri; Marine Vuillermet; Kellen Parker van Dam; Shelece Easterday; Françoise Rose; Alena Witzlack-Makarevich; Kevin Baetscher; Oscar Cocaud-Degrève; Anna Graff; Selma Hardegger; Thomas C. Huber; et al. (Scientific Data)
Abstract The Areal Typology of Languages of the Americas (ATLAs) database encodes 265 linguistic features from 17 different featural domains across 220 North and South American languages and 105 languages in the rest of the world. The domains covered in the database were chosen for their regional relevance, and languages were selected on principles of both phylogenetic diversity and geographic coverage. The features of ATLAs are designed to be logically independent, maximizing the reusability of the data for analytical tools which assume logical independence.